Research on navigation and positioning algorithm for intelligent following vehicle based on UWB - Hu Haibing; Zhang Wenda; Zheng Xipeng; Zeng Guiling (Dianzi Jishu Yingyong, 2019)
The accuracy of intelligent vehicle positioning in the current market cannot satisfy customers′ needs. The positioning algorithm based on Ultra Wideband(UWB) was proposed in order to solve the problem. Two fixed anchors were placed on the intelligent positioning vehicle. The data of distance from the tag to the two anchors was caculated by Kalman filter algorithm. The trigonometric function was used to get the distance from the tag to the middle point of the two anchors and the offset angle. Then the distance and angle data were transmitted to the motor control module, which adjusted Pulse Width Modulation(PWM) value through Proportion Integration Differentiation(PID) algorithm to control the speed and directions of the motor. Experimental results show that the distance deviation is less than 9 cm and the angle deviation is less than 10 degrees by this method, which proves that intelligent vehicle positioning is more accurate than before.